(3QSGdI aj fSHI GdJCdjas - (3aNQ GdOjf CHj fUQ eMeO Hf eMeO Hf Ydj GdNLfOj, aNQ GdedI,J (B703 (3g` s ((3TGg LfGHGO GdgfO s)
(3ChdgG (B:s
(3deG cGfJ GdfSHI GdehSjbjI fhYkG eNUhUkG ef GdfSH hGdWHjYI GdfhYjI dGJJMUd ai GdBYjGf hGdCPgGf s
(3BNQgG (B:s
(3hdfbJUQ Ydi gPG GdbOQ ef gPg GdMGTjI MGeOjf Gddg hTGcQjf dCfYeg s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeg (B- (3U (B59 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeJMa GdHQjWGfi (B(OR2361) s
Keywords: (3GdehSjbi hGdZfGAs